Bases teórico-metodológicas para a elaboração de um dicionário português-espanhol de economia - Silva, Odair Luiz Nadin da [UNESP] (2011)
The aim of this article is to present the theoretic-methodological bases for the construction of a bilingual terminological dictionary of economics which serves either Portuguese and Spanish speakers. Th e contrasted languages are the Brazilian Portuguese variety and the peninsular and Argentinean varieties. The purpose of this text is based on the principles of the Communicative Theory of Terminology - CTT (Cabré, 1999).